Surface Modification and Bioactivity of Anodic Ti6Al4V Alloy - Saharudin, Khairul Arifah; Sreekantan, Srimala; Abd Aziz, Siti Nor Qurratu Aini; Hazan, Roshasnorlyza; Chin, Wei Lai; S. M. N. Mydin, Rabiatul Basria; Mat, Ishak (American Scientific Publishers, 2013)
The present study deals with surface modification of Ti6Al4V alloy via anodization technique. The morphology, structure, adhesion and bioactivity of Ti6Al4V alloy after anodization process were investigated in detail. The influence of fluoride content and direct circuit (DC) applied voltage during anodization of Ti6Al4V alloy in a bath with electrolytes composed of ethylene glycol (EG) and ammonium fluoride (NH4F) were considered. It was found that the average pore sizes and length of nanoporous or nanotubes were increasing with the fluoride content and applied voltage. A minimum of 3 wt% of NH4F is required to grow a self-organized nanotube arrays. As the fluoride content was increased to 5 wt%, TiO2 nanotubes with average diameter of 110 nm and 3.4 microm lengths were successfully synthesized. It is noteworthy to point out that the rate of the nanotube formation was increasing up to 9 microm thick bioactive TiO2 nanotubes layer as anodization time was increased to 3 h. Based on the results obtained, the PA6 cells cultured on anodic Ti6Al4V alloy showed highest level of cell viability and greater cell adhesion compared to the flat Ti6Al4V foil substrate. In fact, highly ordered nanotubes structure on Ti6Al4V alloy can provide beneficial effects for PA6 cells in attachment and proliferation.